Analysis of financial methods of environmental management regulation in the context of harmonization of Ukrainian and European financial instruments - O.M. (Економіка, управління та адміністрування)
One of the key challenges facing humanity is rapid climate change. The deterioration of the environmental situation is inextricably linked to the development of society, the introduction of modern technologies, and the expansion of business activities. This requires the immediate intervention of government agencies, international and regional organisations, and private entities to address this problem. The issue of environmental management is currently of particular concern and is in the focus of many institutions, including the European Union, which is constantly improving the ways and mechanisms for its regulation. As Ukraine plans to become a member of the EU, harmonisation of our legislation, including in this area, is a prerequisite for integration. Therefore, the purpose of the article is to study financial methods of environmental regulation in the EU and to determine the effectiveness of their operation and prospects for adaptation in Ukraine. The following methods were used in writing the article: analysis, synthesis, generalisation, systematisation, and specification. This paper focuses on financial methods, as they are the most effective. It is established that the financial instruments of environmental management regulation include: taxes and fees, emissions trading, compensation for the use of natural resources, bonuses and subsidies, cost of environmental restoration, environmental loans, green investments and encouragement of innovation. For European integration, Ukraine needs to broaden the tax base for environmental taxes. It is also necessary to review the rate of the environmental tax on carbon emissions, which is currently significantly lower than in the EU. Increasing it would allow exporters of goods to the European Union to avoid paying the difference in CIT and use the savings to address environmental issues. In Ukraine, unlike European practice, a significant drawback is that rents for the use of subsoil, water, forest resources, and oil pipelines are not considered environmental taxes and are not used for environmental protection measures. Funding for environmental restoration should be made taking into account all factors of influence for each specific region and the country as a whole. Investments in environmental modernisation can be one of the most effective financial instruments for Ukraine, as they are based on incentives rather than coercion. Thus, environmental management regulation in Ukraine requires reforming financial methods in accordance with the requirements of European legislation.